Fluorescence Microscopy: A Concise Guide to Current Imaging Methods. Issue 1 (13th February 2018) - Combs, Christian A.; Shroff, Hari
Abstract: The field of fluorescence microscopy is rapidly growing and offers ever more imaging capabilities for biologists. Over the past decade, many new technologies and techniques have been developed that allow for combinations of deeper, faster, and higher resolution imaging. These have included the commercialization of many super‐resolution and light sheet fluorescence microscopy techniques. For the non‐expert, it can be difficult to match the best imaging techniques to biological questions. Picking the most appropriate imaging modality requires a basic understanding of the underlying physics governing each of them, as well as information comparing potentially competing imaging properties in the context of the sample to be imaged. To address these issues, we provide here concise descriptions of a wide range of commercially available imaging techniques from wide‐field to super‐resolution microscopy, and provide a tabular guide to aid in comparisons among them. In this manner we provide a concise guide to understanding and matching the correct imaging modality to meet research needs. © 2017 by John Wiley & Sons, Inc.